The Influence Of Hypnobreasfeeding On Breast Milk Explosion In Public Women At The Karnila Nasution Midwifery Clinic, Panyabungan District, Mandailing Natal District - Dewi Srirahayu Tinendung; Khoirunnisa’a Batubara (Sean Institute, 2023)
One of the keys to success in breastfeeding is the mother's confidence and intention to be able to breastfeed her baby. Unfortunately, not all mothers have a calm mind or always think positively about breastfeeding their babies. If the mother is stressed and has negative thoughts, the work of the hormone oxytocin will be hampered. To overcome this, hypnobreasfeeding therapy can be done. The aim of this research is to determine the effect of hypnobreastfeeding techniques on breast milk production during the postpartum period. This type of research is quantitative using the experimental method with a two group pre-test and post-test design research design approach. The population is all postpartum mothers who have difficulty breastfeeding their children, totaling 20 people. The sampling technique for this research is to use a total sampling technique. Data collection uses questionnaires and observation sheets. Data analysis used the Wilcoxon test. The results of research on breast milk production before the hypnobreastfeeding technique was carried out were mostly in the insufficient category (70%), while in the post-intervention phase, the largest distribution was in the sufficient category (75.0%). The Wilcoxon test results show a p value = 0.003, so it can be interpreted that there is a difference in the smoothness of breast milk production between before and after the hypnobreastfeeding technique. The conclusion of this research is that there is a positive influence of hypnobreasfeeding on breast milk production in postpartum mothers. It is hoped that health workers can provide services for maternal health at the clinic and can provide education on hypnobreasfeeding techniques to increase breast milk production.